The Stability of the Chitosan Coating on Polyester Fabric in the Washing Process - Tanja Pušić; Tea Kaurin; Marko Liplin; Ana Budimir; Mirjana Čurlin; Katia Grgić; Ana Sutlović; Julija Volmajer Valh (Tekstilec)
The sensitivity of chitosan to environmental conditions and processing conditions can stress its structure and cause degradation of this polymer on various application carriers. The stability of chitosan in a designed textile structure of standard polyester fabric with chitosan was analysed in a multiple washing process with a standard detergent by studying the properties before and after 10 washing cycles. The chitosan was coated on standard and alkali treated polyester fabrics. Washing was performed with an ECE A reference detergent at 60 °C according to the Standard protocol HRN EN ISO 6330 in 10 cycles. The washing stability of chitosan onto polyester fabrics was monitored by a staining test, zeta potential, breaking force, breaking elongation, pilling propensity, touch, whiteness, moisture transport, antimicrobial activity and morphological features. The staining test confirmed the wash stability of chitosan coated on alkali hydrolised polyester fabrics, while the chitosan coated on standard polyester fabric disappeared. Zeta potential proved to be the significant parameter for determining chitosan` stability. The tensile properties of fabric samples were harmonised with other characterisation parameters. Coating of polyester fabric with chitosan increased the elasticity of all samples. The antimicrobial activity of polyester fabrics coated with chitosan against Staphylococcus aureus was reduced by 20% after 10 washing cycles. All the characterisation parameters proved that polyester fabric as a chitosan carrier should be surface modified for designing a stable bioactive textile structure of chitosan and polyester.